2012
DOI: 10.1016/j.tetlet.2012.03.073
|View full text |Cite
|
Sign up to set email alerts
|

Eucalyptals D and E, new cytotoxic phloroglucinols from the fruits of Eucalyptus globulus and assignment of absolute configuration

Abstract: Two new phloroglucinols, named eucalyptals D (1) and E (2), along with a related known compound (euglobal-In-3, 3) were isolated from the fruits of Eucalyptus globulus. Their structures were established on the basis of extensive spectroscopic studies, revealing that they share a common 3,5-diformyl-isopentyl phloroglucinol unit, but each is instead coupled to a different sesquiterpenoid skeleton (aromadendrene in 1, cadinene in 2, and a spirosesquiterpene in 3). Compound 1 possessed an unusual seven-membered D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Meanwhile, the remaining two degrees of unsaturation and the observed four oxygenated carbons at C-3′, C-6, C-10, and C-11 ( δ C 168.4, 85.8, 71.2, and 74.6, respectively) revealed that there were two oxygen bridges in 2 . The diagnostic downfield shift of C-6 ( δ C 85.8) revealed its ether linkage to the deshielding benzene ring101117, and consequently the oxygen bridge between C-10 and C-11 was established to fulfil the unsaturated degree18. The ROESY correlations (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Meanwhile, the remaining two degrees of unsaturation and the observed four oxygenated carbons at C-3′, C-6, C-10, and C-11 ( δ C 168.4, 85.8, 71.2, and 74.6, respectively) revealed that there were two oxygen bridges in 2 . The diagnostic downfield shift of C-6 ( δ C 85.8) revealed its ether linkage to the deshielding benzene ring101117, and consequently the oxygen bridge between C-10 and C-11 was established to fulfil the unsaturated degree18. The ROESY correlations (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…3) of H-6/H-8′a, H-6/Me-15, H-6/H-8 β , H-8 α /Me-12, and H-12′/H-7 revealed the α -oriented H-7′ and the β -oriented H-6, H-7, Me-14, and Me-15. In order to determine its absolute configuration, quantum chemical electron circular dichroism (ECD) calculation was applied1017, and indicated the 4 R , 6 R , 7 R , 10 S , and 7′ R configurations (Figure S1). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Amber* force field was used to define the initial geometries followed by PM6 [22] semiempirical optimizations. These conformers were subsequently used in hybrid DFT B3LYP/6-31G(d,p) calculations to obtain more accurate geometries in the gas phase and in MeCN employing the Conductor-like Polarizable Continuum Model [23,24]. The 24 lowest-energy conformers (Conformer 1-24, see Supplementary data 2) within an energy window of 50 kJ/mol were compared to the minimum-energy conformer which exhibited different intramolecular hydrogen bond interactions, involving the C-1 and C-3′ hydroxy groups and the C-12′ ester oxygen atoms.…”
Section: Resultsmentioning
confidence: 99%